Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Pada Dinas Perdagangan Kota Sorong - Ahmad Jamil; Ramli Lewenussa; Taufik Nur Ramdhani (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
This research aims to analyze the effect of work discipline and work environment on employee performance at the Trade Office of Sorong City. The data of this study were obtained from a questionnaire (primary) and several observations and direct interviews with related parties at the Department of Trade. This research is a quantitative research using a descriptive approach. The findings of this study indicate that work discipline and work environment have a significant positive effect on employee performance. The most dominant variable affecting employee performance at the Trade Office of Sorong City is work discipline, the reason is because the work discipline variable has the largest comparison compared to other variables